FUNGSI DAN TUGAS LEMBAGA PEMASYARAKATAN DALAM MELAKUKAN PEMBINAAN TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN TANJUNG GUSTA KELAS I MEDAN - Ica Karina (Jurnal Profil Hukum, 2025)
Correctional Institutions are a development system that uses an approach that focuses on the potentials of prisoners and the community, so that the community is involved in developing and integrating prisoners into the community and is called the "Developing Community". Tanjung Gusta Class 1 Medan Correctional Institution views prisoners as not objects but as subjects of development who essentially commit unlawful acts due to the rift in the relationship between life, living and livelihood. Correctional Institutions are closely related to "rehabilitation" and "resocialization". Rehabilitation” and “resocialization” are closely related to the implementation of the correctional system. In this case, it attempts to socialize prisoners so that they become good and useful citizens. The implementation of “resocialization” is actually not an easy job because the prisoners being handled have different criminal backgrounds. The correctional system for prisoners is implemented from the examination process to guidance in correctional institutions. Guidance in correctional institutions is central to achieving the success of this guidance. Good and successful guidance is continued by obtaining “rehabilitation”, and finally society can accept them back.